1981
DOI: 10.1111/j.1365-2125.1981.tb01104.x
|View full text |Cite
|
Sign up to set email alerts
|

Ibopamine (SB 7505) in normal subjects and in chronic renal failure: a preliminary report.

Abstract: 1 Pharmacological and experimental studies have shown that ibopamine (SB 7505, di-isobutyric ester of N-methyldopamine) is capable of increasing renal blood flow, diuresis, urinary sodium, potassium and creatinine excretion. 2 SB 7505 was given to twelve volunteer patients, six of whom had normal renal function and six with various degrees of chronic renal impairment. 3 In both groups the drug yielded a prompt increase in urinary excretion of water, sodium and potassium, while creatinine clearance was also see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…The lack of changes in gastric acid secretion in normal volunteers after ibopamine is not easily explained. The doses employed in the present study exert a marked stimulation of dopamine receptors, as suggested by the findings of positive inotropic effects and increase in diuresis (Dei Cas et al, 1982;Stefoni et al, 1981) and prolactin inhibition (Ferrari et al, unpublished data) were observed after administration of the same ibopamine doses. Since it has been suggested that gastric acid secretion might be controlled by a dual dopaminergic effect, a peripheral inhibitory and a central nervous system stimulatory action, the lack of effect observed after ibopamine might be due to a partial crossing of the blood brain barrier by the drug.…”
Section: Discussionsupporting
confidence: 73%
“…The lack of changes in gastric acid secretion in normal volunteers after ibopamine is not easily explained. The doses employed in the present study exert a marked stimulation of dopamine receptors, as suggested by the findings of positive inotropic effects and increase in diuresis (Dei Cas et al, 1982;Stefoni et al, 1981) and prolactin inhibition (Ferrari et al, unpublished data) were observed after administration of the same ibopamine doses. Since it has been suggested that gastric acid secretion might be controlled by a dual dopaminergic effect, a peripheral inhibitory and a central nervous system stimulatory action, the lack of effect observed after ibopamine might be due to a partial crossing of the blood brain barrier by the drug.…”
Section: Discussionsupporting
confidence: 73%
“…The cardiac and peripheral vascular activity of ibopamine is complemented by its activity on the kidney Ghirardi et al, 1980;Longhini et al, 1983;Merlo et al, 1979;Stefoni et al, 1981;. This combined action on the myocardium, after-and pre-load, tends to improve cardiac performance and the haemodynamic pattern in CHF.…”
Section: Discussionmentioning
confidence: 99%
“…The positive inotropic and diuretic effects of ibopamine in animals and in man have been reported in several publications Melloni etal., 1981;Merlo et al, 1979Merlo et al, , 1982Stefoni et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…This dose also lacked a significant effect on water and electrolyte excretion. Despite the difference in study design the impressive results of Stefoni et al (1981) led us to anticipate a measurable effect on renal function from single doses of ibopamine. An important difference in the Italian study was the continued administration of ibopamine for a period of 7 days.…”
Section: Discussionmentioning
confidence: 99%